ACLY as a modulator of liver cell functions and its role in Metabolic Dysfunction-Associated Steatohepatitis - Convertini, Paolo; Santarsiero, Anna; Todisco, Simona; Gilio, Michele; Palazzo, Donatella; Pappalardo, Ilaria; Iacobazzi, Dominga; Frontuto, Maria; Infantino, Vittoria (Journal of translational medicine, 2023)
Background Non-alcoholic Fatty Liver Disease (NAFLD), now better known as Metabolic (Dysfunction)-Associated Fatty Liver Disease (MAFLD) and its progression to Nonalcoholic Steatohepatitis (NASH), more recently referred to as Metabolic (Dysfunction)-Associated Steatohepatitis (MASH) are the most common causes of liver failure and chronic liver damage. The new names emphasize the metabolic involvement both in relation to liver function and pathological features with extrahepatic manifestations. This study aims to explore the role of the immunometabolic enzyme ATP citrate lyase (ACLY), with a critical function in lipogenesis, carbohydrate metabolism, gene expression and inflammation. Methods ACLY function was investigated in TNFα-triggered human hepatocytes and in PBMC-derived macrophages from MASH patients. Evaluation of expression levels was carried out by western blotting and/or RT-qPCR. In the presence or absence of ACLY inhibitors, ROS, lipid peroxidation and GSSG oxidative stress biomarkers were quantified. Chromatin immunoprecipitation (ChIP), transient transfections, immunocytochemistry, histone acetylation quantitation were used to investigate ACLY function in gene expression reprogramming. IL-6 and IL-1β were quantified by Lumit immunoassays. Results Mechanistically, ACLY inhibition reverted lipid accumulation and oxidative damage while reduced secretion of inflammatory cytokines in TNFα-triggered human hepatocytes. These effects impacted not only on lipid metabolism but also on other crucial features of liver function such as redox status and production of inflammatory mediators. Moreover, ACLY mRNA levels together with those of malic enzyme 1 (ME1) increased in human PBMC-derived macrophages from MASH patients when compared to age-matched healthy controls. Remarkably, a combination of hydroxycitrate (HCA), the natural ACLY inhibitor, with red wine powder (RWP) significantly lowered ACLY and ME1 mRNA amount as well as IL-6 and IL-1β production in macrophages from subjects with MASH. Conclusion Collectively, our findings for the first time highlight a broad spectrum of ACLY functions in liver as well as in the pathogenesis of MASH and its diagnostic and therapeutic potential value. Graphical Abstract